Nghiên cứu điện cực anot trơ hỗn hợp oxit kim loại cho bảo vệ catot chống ăn mòn vỏ tàu biển - Phong, Phạm Ngọc; Linh, Đỗ Chí; Hạnh, Phạm Hồng; Ngọc, Phạm Xuân (Vietnam Journal of Chemistry, 2017)
The corrosion of metals ship hull occurs when it contacts with an marine environment and causes risk and great losses from the economic point of view. The research of using mixed metal anodes (MMO) for ship hull cathodic protection by impressed current has been carried out. The influence of various factors such as: anode current density, salt concentration and flow rate of solution on anode stablity has been examined. It was found that the anode MMO Ti/IrO2/RuO2IrO2TiO2 coud be used at high current density up to 600 A/m2 in 3.5 % NaCl solution and the anode stability decreased in solution of low concentration 0.2 % NaCl. The flow rate of solution has not almost influence on anode stability. Keywords. Mixed metal anode MMO, cathodic protection by impressed current, corrosion of ship hull, current density.